Annual performance of a solar aided coal-fired power generation system (SACPG) with various solar field areas and thermal energy storage capacity. (1st November 2015) - Wu, Junjie; Hou, Hongjuan; Yang, Yongping; Hu, Eric
Highlights: Solar aperture area and energy storage capacity for SACPG system is optimized. Three typical turbine loads of SACPG systems are simulated. SACPG system is simulated with real hourly meteorology data. Improved matrix thermal balance equation is used in SACPG system models. Efficiency decrease due to off-design behavior and solar input is considered. Abstract: Integrating solar energy into a conventional fossil-fuel fired power plant through solar-aided coal-fired power generation (SACPG) mechanism has been proven to be an efficient way to use solar energy for power generation purposes. However, due to the rather intermittency of solar radiation, SACPG systems always work under off-design conditions. In this paper, hourly based annual performances of a SACPG system was simulated and analyzed with various solar field sizes and thermal energy storage (TES) capacity under different (plant) load conditions in a 330 MW power plant case study. The results indicate that, TES system could stabilize the solar thermal output and improve the stability of the SACPG system at different loads. And it could also improve solar contribution in the power generation and annual peak solar-to-electricity efficiency. Through case study, the minimum levelized energy of costs and corresponding aperture area in this case are 0.0629/kW h, 1.413 × 10 5 m 2 for 100% load, 0.0654/kW h, 9.42 × 10 4 m 2 for 75% load, and 0.0730/kW h and 5.89 × 10 4 m 2 for 50% load, respectively. And the corresponding optimized TES hour with different loads is found to be 0.5 h. The values are relatively lower than the reference trough plant.